Gender as a Political Instrument Forming New Boundaries by Ethnic and Religious Diasporas in European Union - Sharov, Konstantin S. (Springer Nature Singapore : Imprint: Springer, 2022)
XVII, 226 p. 64 illus., 47 illus. in color.